Kierkegaard in France: A History of Reception and Influence - Becker-Lindenthal, Hjördis; Sackin-Poll, Andrew (New Research in the History of Western Philosophy, 2025)
Why does Kierkegaard's thought remain vital in French philosophy and theology? Kierkegaard in France traces the dynamic evolution of Kierkegaard's reception from the early 20th century to contemporary debates on faith, ethics, and individuality. His influence on French thought is examined anew with regard to well-known thinkers like Jean-Paul Sartre, Jacques Derrida, and Paul Ricœur, as well as readings that have largely been overlooked, like those by Simone de Beauvoir and Vladimir Jankélévitch. From existentialism and phenomenology to poststructuralism and feminism, Kierkegaard continues to be an essential interlocutor in shaping the 'continental' tradition of thought in France. There is a natural affinity between Kierkegaard's uniquely intense, subjectively-involved metaphysical realism and the French spiritualist tradition which eschews both idealism and reductive empiricism. This book brings out that affinity and displays it in all the variety of its manifestations, both religious and secular, both speculative and existentialist. An indispensable and monumental entry for scholars and intriguing read for a wider audience. -Catherine Pickstock, Norris-Hulse Professor of Divinity, University of Cambridge